Characterization of hippocampal CA1 place cells. - Lau, Hwee Hui. (2013)
In 1971, O’Keefe & Dostrovsky discovered the highly selective firings of hippocampal principal cells when rats were in specific regions within an environment and prompted research on hippocampus role in spatial processing. In this study, rats were pre-trained in a square box prior to surgical implantation of microdrives into the brain for extracellular recording in the hippocampal CA1 pyramidal layer. A total of 9 recorded neurons displayed place cell properties. These neurons possessed unique place fields which were stable across sessions within the same environment, and discharged of action potential by a neuron is highly associated to the position the rat was in. Remapping of place fields were observed when rats were introduced into a novel environment. Results show that the physiologically identified neuron can have 1 or more place fields. Most of the neurons had stable firing across sessions recorded in both familiar and novel environments, while some showing selective discharged of spikes in either one of the environments tested. The data recorded had provided spatial-temporal pattern for study of neuronal activities of physiologically identified place cells residing in the hippocampal CA1 pyramidal layer.